ANALISIS PERUBAHAN TUTUPAN LAHAN DI STASIUN PENELITIAN FAKULTAS KEHUTANAN UNIVERSITAS KUNINGAN WILAYAH TAMAN NASIONAL GUNUNG CIREMAI - Ayu Ratna Dewi Utami; Iing Nasihin; Dede Kosasih (Faculty of Forestry and Environment, Universitas Kuningan, 2022)
The Research Station of the Faculty of Forestry, Universitas Kuningan is located at an altitude of 1,100- 1,175 masl which is in the rehabilitation zone and close to the jungle zone of Mount Ciremai National Park. This area is a degraded location due to land clearing for agricultural cultivation activities. The existence of this research station aims to support the function of the area. The strategic management plan must be in accordance with the objectives of the area management, so to manage the research station requires land cover information. So that research related to land becomes important to do. The method used is a field crosscheck, which will be tested for accuracy with an accuracy test, land cover classification on recorded images in 2009, 2013, 2019 and 2021 with the Supervised Classification interpretation method. The results showed that the accuracy test had an overall accuracy of 83.37% and kappa accuracy of 77.55%, from the results of image classification in 2009 in the research station area which consisted of 3 classes, namely field, mixed forest and pine forest. Meanwhile, in 2013 there were 5 land cover classes, namely rice fields, shrubs, calliandra, pine and mixed forest. The years 2019 and 2021 consist of calliandra, scrub, pine and mixed forest. This change is caused by changes due to biophysics and changes due to socio-economic conditions, thus causing changes in land cover in the forest area of Kuningan UniversityStasiun Penelitian Penelitian Fakultas Kehutanan Universitas Kuningan terletak pada ketinggian 1.100-1.175 mdpl yang berada di zona rehabilitasi dan dekat dengan zona rimba Taman Nasional Gunung Ciremai. Kawasan ini merupakan lokasi yang terdegradasi akibat pembukaan lahan untuk kegiatan budidaya pertanian. Keberadaan stasiun penelitian ini bertujuan untuk mendukung fungsi kawasan . Rencana strategis pengelolaan harus sesuai dengan tujuan pengelolaan kawasan, sehingga untuk mengelola stasiun penelitian membutuhkan informasi tutupan lahan. Sehingga penelitian yang berkaitan dengan lahan menjadi penting untuk dilakukan. Metode yang digunakan adalah crosscheck lapangan, yang akan diuji akurasinya dengan uji akurasi, klasifikasi tutupan lahan pada citra rekaman tahun 2009, 2013, 2019 dan 2021 dengan metode interpretasi Supervised Classification. Hasil penelitian menunjukkan bahwa uji akurasi memiliki akurasi keseluruhan sebesar 83,37% dan akurasi kappa sebesar 77,55%, dari hasil klasifikasi citra tahun 2009 di kawasan stasiun penelitian yang terdiri dari 3 kelas yaitu lapangan, campuran hutan dan hutan pinus. Sedangkan pada tahun 2013 terdapat 5 kelas tutupan lahan yaitu sawah, perdu, kaliandra, pinus dan hutan campuran. Tahun 2019 dan 2021 terdiri dari kaliandra, semak belukar, pinus dan hutan campuran